Effect Of Job Satisfaction On Citizenship Behavior Organizational Commitment Ministry Of High School Education In Timor-Leste - Cesaltino Alves Ximenes; I Gede Riana; Pedro M.B. Ximenes (LPPM Institut Teknologi dan Sains Mandala, 2022)
In every country there must be an organization formed with a different vision and mission. The organization itself is defined as a forum for people who have the same goal, be it for social services, the welfare of members or for profit. In the process of achieving its goals, an organization must pay attention to its resources, be it human resources, financial resources, materials, as well as technological and system capabilities. OCB is a optional behavior that is not part of an employee's formal work obligations, but supports the effective functioning of the organization. The Ministry of Education of Timor Leste is required to always provide excellent service and has a commitment to improve quality. service and quality of education. Organizational Citizenship Behavior (OCB) is an individual contribution that exceeds the demands of the role in the workplace and is rewarded by the achievement of task performance. This OCB involves several behaviors including helping others, volunteering for extra tasks, obeying the rules and procedures in the workplace. This research is a quantitative research. The data sources in this study are primary data and secondary data. The sample used in this study was 144 The population of civil servants under the Ministry of Education of Timor Leste is 144 people. The sampling technique used was a saturated sample, that is, all of the population was used as a sample. As for the level of explanation (level of clarity) this researcher uses an associative problem formulation. The data collection method uses a questionnaire (questionnaire) and the data analysis techniques used in this study are the classical assumption test, hypothesis testing, and multiple linear regression analysis.